Free speech, ban and “fatwa”: a study of the Taslima Nasrin affair - Hasan, Md. Mahmudul (Routledge, 2010)
Of the many feminist voices in Bangladesh, Taslima Nasrin is the best known for the censorship, fatwa and subsequent legal intervention against her. Of all her banned books, Lajja drew the widest international attention, and that, as many commentators argue, was especially because of the involvement of the Indian establishment and media that sought to distract the world’s concern away from religious tensions and communal strife in India in the wake of the Babri Masjid’s demolition in 1992. Despite this political debate, the Taslima Nasrin affair is sometimes used to reinforce the binary between Islam and free speech, and the writer represented as a wronged woman of Bangladesh’s Islamic patriarchy. However, a look at the genealogy of the Bangladesh Penal Code and the Islamic position on free speech suggest that Bangladeshi censorship laws date back to the British colonial period and that there is a wide gap between the street rhetoric to punish Nasrin as an “apostate” and “blasphemer” and the Islamic tradition of free speech rights. Moreover, shifting ban controversies from Lajja to Ka/Dwikhandita counteracts the conventional branding of the secular as sole defenders of free speech and the religious as its chief opponents.